Turkish validity and reliability study of the flow experience scale in video games - Mert Erkan; Osman Goktug Kocak; Ozdemir Ahmet Nar; Erdem Turan (Ozlem Book Center, 2023)
The purpose of the present study was to adapt the "Scale of Flow Experience in Video Games" to Turkish language and culture. The "Scale of Flow Experience in Video Games", which can reveal a lot of data such as identifying customer potential and revealing the interests of individuals by providing detailed information about those who are exposed to a video game as service providers, viewers or participants in the video game industry, and offers the opportunity to segment the extent to which video game players are affected by video games and to which extent they continue to play games depending on which effects. Since there is no measurement tool that can evaluate the flow levels of video game players in Turkish, we believe that this study will contribute to the literature. The research population consisted of a total of 334 individuals selected by convenience sampling method in the city of Eskişehir. Confirmatory Factor Analysis (CFA) was used to test the construct of the scale. As a result of the analysis, we found that the scale was above the values given in the literature for fit and showed good fit. In addition, the construct validity of the scale was tested. The Cronbach's Alpha (0.969) internal consistency coefficient for the reliability of the scale consisting of 9 dimensions and 28 items was above the threshold given in the literature. Based on the findings, we determined that the "Scale of Flow Experience in Video Games" is a valid and reliable measurement tool. Therefore, it was concluded that the measurement tool, which shows the necessary psychometric properties for Turkish language and culture, can be used for activity participants in Turkey.